The Effect of the Sociology of Religion on Theology, a Holy Struggle for Power: A Mini-Festschrift - Mol, Hans (Journal of Christian education, 2007)
Jesus' kingdom involves suffering and self-denying service, unlike the power hierarchy of a worldly order. In his commentary on Matthew, Calvin saw that holy organizations are not free from corruption, and that power is a dangerous thing. In his commentary on Isaiah 42:1-9, Christ is the humble servant who came to bring the world under God's authority. Christ also represents peace, reconciling those separated from God or one another. How relevant are these bible references, and Calvin's comments for our day? (It is intriguing that Calvin reproved those who did not use ‘the works of the ungodly’ in physics, symbiotics, mathematics, etc). Mol would add (for Calvin) anthropology, psychology, sociology and political science. The areas of relevance are:Disorder and conflict minimization, where selfishness and pride endanger the social bond, whereas self-denial strengthens it.The global mission of the faith, associated with which are language- learning, health and education facilities, and the well-being of the poor.Organizational corruption, when social science organizations ‘bend’ content to suit their ends, and functional questions are not entertained.